Peran Subak dalam Memanajemen Perilaku Petani untuk Mewujudkan Pertanian Berkelanjutan di Bali - Ni Putu Sukanteri; I Gusti Ayu Diah Yuniti; I Made Suryana; Yenny Verrawati (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
Subak is a farmer organization that regulates the irrigation system for rice cultivation in Bali. The research examines the behavior (knowledge, attitudes, skills) of subak members within the framework of the Hindu religious philosophy of Tri Hita Karana, three forms of harmony, namely spiritual, social, and environmental. The case study was conducted in Subak Aseman III, Selemadeg Timur District, Tabanan Regency. This study applies a qualitative method with data collection techniques by observation, interviews, and literature review. The results showed that the behavior of farmers in mastering knowledge was obtained both formally and informally. Farmers are selective in accepting various technological innovations. In implementing the values ??of Tri Hita Karana, subak members carry out rituals on auspicious days to pray for a better harvest result, maintain social harmony through collective decision making, and preserve the environment. This spirit in implementing the Tri Hita Karana philosophy is in line with the spirit to realize sustainable agriculture.